2012
DOI: 10.1073/pnas.1212584109
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional influence of sodium channel activation on NMDA receptor–dependent cerebrocortical neuron structural plasticity

Abstract: Neuronal activity regulates brain development and synaptic plasticity through N-methyl-D-aspartate receptors (NMDARs) and calciumdependent signaling pathways. ]. Pharmacological evaluation showed that PbTx-2-induced Ca 2+ influx primarily involved VGSC activation and NMDAR-mediated entry. Additionally, PbTx-2 robustly potentiated NMDA-induced Ca 2+ influx. PbTx-2-exposed neurons showed enhanced neurite outgrowth, increased dendritic arbor complexity, and increased dendritic filopodia density. The appearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…A K v 3.1-selective, low concentration (30 mM) of 4-AP also enhanced cerebrocortical neuron neurite outgrowth. The similar bidirectional patterns shown by NMDA (George et al, 2012) and gambierol on neurite outgrowth are consistent with a role for NMDA receptors in the effects of gambierol on cerebrocortical neuron growth. An inverted-U model describes the relationship between NMDA receptor activity and neuronal survival and growth (Lipton and Nakanishi, 1999).…”
Section: Discussionsupporting
confidence: 65%
“…A K v 3.1-selective, low concentration (30 mM) of 4-AP also enhanced cerebrocortical neuron neurite outgrowth. The similar bidirectional patterns shown by NMDA (George et al, 2012) and gambierol on neurite outgrowth are consistent with a role for NMDA receptors in the effects of gambierol on cerebrocortical neuron growth. An inverted-U model describes the relationship between NMDA receptor activity and neuronal survival and growth (Lipton and Nakanishi, 1999).…”
Section: Discussionsupporting
confidence: 65%
“…NMdAR activation mediates calcium influx, cAMP response element-binding protein phosphorylation, and brain-derived neurotrophic factor production, which are necessary to neurogenesis, dendritic plasticity, and synaptogenesis. 7,21,32 Therefore, directly inhibiting NMdARs might be deleterious to animals and human. [6][7][8][9][10] NMdAR activity is unaffected by genetically deleting PSd-95 in vivo 33 or by suppressing its expression in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the Na v 1.2 subunit encoded by Scn2a localizes to the axon initial segment in cerebellar granule cells [267] and that pharmacological modulation of voltage-gated sodium channel activity in cortical neurons influences neurite length and complexity as well as density of spines and excitatory synapses [123, 124]. Alternative splicing of Scn2a results in differential expression of the various isoforms during development and adulthood [121], possibly as a means of controlling neuronal excitation.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%